Total lymphocyte count as a surrogate marker for CD4 count in resource-limited settings - Obirikorang, Christian (BioMed Central, 2012)
BACKGROUND: CD4 testing is the recognized gold standard used to stage HIV/AIDS, guide treatment decisions for HIV-infected persons and evaluate effectiveness of therapy. The need for a less expensive surrogate marker that can be used in resource-limited setting is however necessary. The study sought to assess the suitability of Total lymphocyte count (TLC) as a surrogate marker for CD4 count in resource-limited localities in Ghana. METHODS: This observational study was conducted at the Central Regional Hospital, which has one of the established antiretroviral therapy centres in Ghana. A total of one hundred and eighty-four (184) confirmed HIV I seropositive subjects were included in the study. Blood samples were taken from all the subjects for estimation of CD4 and total lymphocyte counts. The study subjects were further categorised into three (3) groups according to the Centers for Disease Control and Prevention (CDC) classification criteria as follows: CD4 counts (1) ≥ 500 cells/mm(3) (2) 200–499 cells/mm(3) and (3) <200 cells/mm(3). Positive predictive value (PPV), negative predictive value (NPV), sensitivity and specificity of various TLC cut-offs were computed for three groups. Correlation and Receiver Operator Characteristic analysis was performed for the various CD4 counts and their corresponding Total Lymphocyte count obtained. RESULTS: The sensitivity, specificity, positive and negative predictive values of TLC 1200 cells/ mm(3) to predict CD4 count were <200 cells/mm(3) 72.2%, 100%, 100% and 95.7% respectively. A TLC of 1500 cells/ mm(3) was found to have maximal sensitivity (96.67%), specificity (100%), PPV (100%) and NPV (75.0%) for predicting a CD4 cell count of 200–499 cell/mm(3). A TLC of 1900 cells/mm(3) was also found to have a maximal sensitivity (98.45%), specificity (100%), PPV (100%) and NPV (100%) for predicting CD4 count ≥500 cells/mm(3). A positive correlation was noted between 184 paired CD4 and TLC counts (r = 0.5728). CONCLUSION: Total Lymphocyte count can therefore adequately serve as a surrogate marker for CD4 count in HIV patients who are naïve for antiretroviral therapy in resource-limited areas.